Epicardial adipose tissue and metabolic syndrome: An update protocol for systematic review and meta-analysis - Roever, Leonardo (Medicine (Baltimore), 2018)
BACKGROUND: The prevalence of metabolic syndrome (MetS) and MetS-related stroke is set to increase dramatically in coming decades. MetS is a complex disease that includes endothelial dysfunction, insulin resistance, diabetes, hypertension, ectopic obesity, and dyslipidaemia, and an increased risk of cardiovascular events. However, there are no systematic analyses, or well-conducted meta-analyses to evaluate the relationship between epicardial adipose tissue (EAT) and (MetS). The aim of this study is to examine this association of EAT with MetS in different ages and sex. METHODS: The update systematic review, and meta-analysis will be conducted using published studies that will be identified from electronic databases (ie, PubMed, EMBASE, Web of Science, and Google Scholar. Studies that firstly, examined the association between EAT and MetS, secondly, focus on cohort, case-control, and cross-sectional studies, thirdly, were conducted among in adults aged between 40 and 70 years, fourth, provided sufficient data for calculating ORs or relative risk with a 95% CI, fifth, were published as original articles written in English or other languages, and sixth, have been published until January year 2018 will be included. Study selection, data collection, quality assessment, and statistical syntheses will be conducted based on discussions among investigators. RESULTS: Ethics approval was not required for this study because it was based on published studies. The results and findings of this study will be submitted and published in a scientific peer-reviewed journal. This study will provide a high quality synthesis on the association of EAT and MetS. CONCLUSION: This systematic review will provide evidence to assess whether there is a strong association of EAT and MetS, and its components.